Effectiveness of entecavir or telbivudine therapy in patients with chronic hepatitis B virus infection pre-treated with interferon compared with de novo therapy with entecavir and telbivudine - Cai, Shaohang (Medicine (Baltimore), 2017)
Little is known about the optimal treatment following the initial failure of interferon therapy and the potential different efficacy with de novo therapy with entecavir (ETV) or telbivudine (LDT) and following the interferon therapy failure. ETV or LDT therapy following the interferon therapy failure was compared with that of de novo therapy with ETV or LDT in patients with chronic hepatitis B virus (HBV) infection. Treatment parameters included virological response, hepatitis B e antigen (HBeAg) seroconversion, and alanine aminotransferase (ALT) normalization. Of 180 patients studied, 56 received de novo telbivudine monotherapy (LDT group); 45 received entecavir monotherapy (ETV group); 40 received LDT following interferon (interferon-telbivudine [IFN-LDT] group); and 39 received ETV following interferon (interferon-entecavir [IFN-ETV] group). At week 52, virological response occurred in significantly more patients in the IFN-ETV group than the ETV group (87.2% vs 57.8%, P = .003). At week 104, HBeAg seroconversion occurred in significantly more patients in the IFN-ETV group than the ETV group (44.4% vs 22.2%, P = .03). At week 52, virological response was achieved by significantly more patients in the IFN-LDT group than the LDT group (85.0% vs 64.3%, P = .02). This study showed that switch to rescue therapy with ETV or LDT therapy after failure of interferon therapy resulted in more rapid virologic response than with de novo treatment with either ETV or LDT; rescue therapy with ETV resulted in a greater HBeAg seroconversion rate.